Students’ Responses and Differences in Learning Motivation after Canva-Based Interactive Ecosystem Learning among Grade X Senior High School Students - Tasya Aliviah; Risma Delima Harahap; Rosmidah Hasibuan (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to examine students’ responses and compare their learning motivation in ecosystem learning after the implementation of Canva-based interactive learning media among tenth-grade senior high school students. The study employed a descriptive-comparative quantitative approach supported by qualitative data. The participants consisted of 60 Grade X students from three classes. All classes received ecosystem instruction using Canva-based interactive learning media. Data were collected through a learning motivation questionnaire, a student response questionnaire, classroom observations, and interviews. The quantitative data were analyzed using descriptive statistics and one-way analysis of variance (ANOVA), while the qualitative data were used to support the interpretation of the findings. The results showed that students generally responded positively to the use of Canva-based learning media. Students reported that Canva helped them understand ecosystem material more easily, increased their interest in learning, enhanced their enthusiasm in completing tasks, and improved classroom interaction. The statistical analysis also revealed a significant difference in students’ learning motivation among the three classes after the implementation of Canva-based learning media, with Class X-3 obtaining the highest mean score. These findings indicate that Canva-based interactive learning media have strong potential to support students’ learning motivation and create a more engaging and student-centered learning environment in ecosystem instruction. However, the extent of its impact may vary across classes depending on classroom conditions and the learning process.